Update on the diagnosis and management of neurocysticercosis - Takayanagui, Osvaldo Massaiti; Haes, Tissiana Marques de (Arquivos de Neuro-Psiquiatria, 2022)
Background: Neurocysticercosis (NCC) is a serious public health problem in several developing countries, including those in Latin America, Asia, and Africa. NCC is considered to be the main cause of late-onset epilepsy in endemic areas. Objective: This review summarizes recent advances in diagnosis and therapy of NCC. Methods: Relevant articles and books were reviewed and used as a source of information for this review. Results: The diagnosis of NCC is based upon neuroimaging studies (MRI and computed tomography) and laboratory analysis of the cerebrospinal fluid (CSF). Praziquantel and albendazole are considered parasiticidal drugs against NCC, but there is an intense debate over the value and safety of these drugs. Conclusion:  Given the relative scarcity of clinical trials, more comparative interventional studies, especially randomized controlled trials in long-term clinical evolution, are required in order to clarify the controversy over the validity of parasitic therapy in patients with NCC.
Keywords: Cysticercosis; Taenia solium; Epilepsy; Magnetic Resonance Imaging; Cerebrospinal Fluid; Albendazole; Praziquantel